Antoni K. Antonowicz as the researcher conducting the study of the writings of Tatars — the Muslims of the Grand Duchy of Lithuania - Łapicz, Czesław (Slavistica Vilnensis, 2016)
The paper is a tribute to a Man and, at the same time, an attempt at a subjective evaluation of the academic achievements of the father of modern kitab studies — professor Antoni Antonowicz of the Vilnius University. The occasion is the 100th anniversary of the discovery of the invaluable manuscript of the Tartars of the Grand Duchy of Lithuania, the so-called the Kitab of Ivan Lutskevich, and the 35th anniversary of professor Antonowicz’s demise. Selected passages from the correspondence exchanged between the professor and Maciej Musa Konopacki, Vilnius-born Polish Muslim and Tartar intellectual are an essential constituent of the paper.